Risk Communication Model For Improving Safety Culture At The National Oil Company - Bambang Sulistyo P; Fatma LESTARI; Marlinda IRWANTI; Puji LESTARI (International Journal of Environmental, Sustainability, and Social Science, 2022)
Communication System  the concept of System or Communication Model to achieve the goal of improving Safety Culture  in the National Oil   Company. Method research  is Mixed (quantitative and qualitative). In this study using Katherine Miller's theory which consists of three system concepts, namely system components, system processes and system properties to analyze communication processes both internally and externally, is necessary to add an analysis of the system concept, namely monitoring and evaluation. The influence of organizational communication variables with communication climate, communication satisfaction and to develop a safety culture with variables: safety climate, situational, safety behavior. Organizational communication is in the very good category (75,07%) communication climate (73,08)%) good category, there is a positive and significant relationship between communication climate and organizational communication); Communication satisfaction of (78,38)%) is in the good category; there is a positive and significant relationship. Communication satisfaction and Organizational Communication. Can find a new communication system or model, namely (Model – SIKATBUKA) is a system or model that can accommodate the interests of leaders and subordinates as well as stakeholders, the surrounding community in resolving communication aspects within of the National Oil Company. This communication model or system will become a standard in the communication system in the implementation of the of National Oil Company and also function as  can detect problems related to communication in the communication system process that appears in the field. The model– SIKATBUKA